Dacryoadenitis as the Initial Presentation of a Natural Killer T-Cell Lymphoma. Issue 6 (November 2017) - Jiménez-Pérez, Juan C.; Jakobiec, Frederick A.; Zakka, Fouad R.; Yoon, Michael K.
Abstract : Primary orbital natural killer T-cell lymphoma (NKTCL) is a rare condition with only a few published cases in the literature. Over 1 month, an 81-year-old man developed progressive left periocular inflammation unresponsive to treatment. Clinical examination and imaging studies demonstrated a left lacrimal gland enlargement. Bilateral anterior uveitis and erythematous nontender cutaneous lesions were also found. Biopsies of the skin and lacrimal gland on the back revealed histopathologic and immunohistochemical findings confirming Epstein–Barr virus-positive NKTCL. Metastatic work up disclosed multifocal involvement in the pancreas, stomach, and chest wall. Palliative treatment consisting of nonanthracycline-based chemotherapy and radiation was instituted, but the patient died 5 months after the onset of symptoms. This is the first example of acute dacryoadenitis, and the second of bilateral anterior uveitis, in the setting of NKTCL. Absence of naso-sinus involvement in the current case is rare in NKTCL. Despite treatment, the prognosis remains dismal. Orbital specialists should include NKTCL in the differential diagnosis of lacrimal gland/orbital masses and perform an incisional biopsy if the clinical scenario so dictates. Abstract : Orbital natural killer T-cell lymphoma without nasal involvement is rare, an example of which uniquely presented as inflammatory dacryoadenitis with bilateral uveitis.